Perancangan UI/UX Aplikasi Mobile Produk Fashion Pria pada Toko Celcius di Kota Manado Menggunakan Design Thinking - Istiqomah Br Karo Sekali; Chriestie E.J.C Montolalu; Siska Ayu Widiana (PT. SNN MEDIA TECH PRESS, 2023)
Technology is always growing rapidly from year to year, one of which is the internet. This increasingly advanced technology makes it easier for humans to help their activities such as in the field of sales. Celcius is a shop that sells mens products and accessories. Celcius must make online sales via Instagram and Whatsapp. However, purchases via Instagram experience several problems, namely that buyers have to type manually via Instagram and WhatsApp, making it difficult for buyers when buying at Celsius stores. This research aims to create a User Interface (UI) and User Experience (UX) design that makes it easy for buyers to make purchases and find out information about products clearly by using the Design Thinking method which includes the Empathize, Define, Ideate, Prototype and Testing stages. The Design Thinking method used is to create solutions based on problems in order to create designs that are easy to use and understand by users. The design was tested using Usability testing to 10 respondents by presenting a single ease question (SEQ) which obtained a result of 6.85 out of 7 and the System Usability Scale (SUS) which obtained a result of 95 out of 100. Thus, it is concluded that the UI / UX design of mobile-based men's fashion product applications at Celcius stores in Manado City can be used easily by users and have a positive experience based on SEQ results and get good satisfaction from users based on SUS results.